PENGEMBANGAN KOLEKSI BERBASIS AKREDITASI PRODI DI PERPUSTAKAAN IAIN PURWOKERTO - Indah Wijaya Antasari; Agoeng Noegroho (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2019)
The collection development consists of community analysis activities, collection development policies, selection, acquisition, weeding, and evaluation. The development of collections based on study program accreditation in the IAIN Purwokerto library consisted of the development of printed collections and digital collections. For printed collections, IAIN Purwokerto uses academic guidelines and course syllabus as one of the library material selection media. The study program bibliography has been made by the librarian of the IAIN Purwokerto library, it will easily be known how many collections support a particular study program. If there are still study programs whose source of information / reference books are few, then it will be a priority in the procurement of the following year. Digital collections are also considered in the IAIN Purwokerto library. In 2017, the bookless service was launched and began subscribing to Proquest as a research information source for lecturers, students and educational staff at the IAIN Purwokerto.